Sequential cleavage of proinsulin by human pancreatic kallikrein and a human pancreatic kininase - ole-MoiYoi, Onesmo (1979)
A pancreatic endopeptidase localized to the β-cells of the pancreas by immunohistochemical techniques has been purified to homogeneity by following its functional and antigenic characteristics as a glandular kallikrein (EC 3.4.21.8). The enzyme gave a single stained band on alkaline disc gel electrophoresis which corresponded in location with the kinin-generating activity eluted from a replicate gel, was of 54,000 molecular weight by gel filtration, was devoid of caseinolytic activity, elicited a monospecific antiserum in a rabbit, and gave a line of complete identity with a single constituent in pancreatic extract, crude urine, and purified urokallikrein when analyzed with monospecific antibody to urokallikrein. The pancreatic glandular kallikrein generated three cleavage products of increasing anodal mobility from bovine and porcine proinsulin, and the presence of pancreatic kininase or bovine carboxypeptidase B increased the quantity of these products. Although the conversion products did not correspond to diarginyl- and monoarginylinsulin, the product of intermediate mobility was also obtained when proinsulin was treated with a low concentration of trypsin in the presence of kininase. The most rapidly migrating product did correspond to desalanylinsulin in the reference standard. Kininase alone had no action on proinsulin, and aprotinin prevented cleavage by kallikrein alone or in combination with kininase. Although the chemical structure of the proinsulin cleavage products has not been established, human pancreatic kallikrein is considered a putative activator of proinsulin because of its location in the β-cell, its preferential action on proinsulin and kininogen as compared to azocasein, and its capacity to generate insulin intermediate products that are further modified by human pancreatic kininase or bovine carboxypeptidase B.